Antidepressant Drugs Effects on Blood Pressure - Calvi, Anna; Fischetti, Ilaria; Verzicco, Ignazio; Belvederi Murri, Martino; Zanetidou, Stamatula; Volpi, Riccardo; Coghi, Pietro; Tedeschi, Stefano; Amore, Mario; Cabassi, Aderville (Frontiers in Cardiovascular Medicine, 2021)
Individuals suffering from depressive disorders display a greater incidence of hypertension compared to the general population, despite reports of the association between depression and hypotension. This phenomenon may depend, at least in part, on the use of antidepressant drugs, which may influence blood pressure through different effects on adrenergic and serotoninergic pathways, as well as on histaminergic, dopaminergic and cholinergic systems. This review summarizes extant literature on the effect of antidepressant drugs on blood pressure. Selective Serotonin Reuptake Inhibitors are characterized by limited effects on autonomic system activity and a lower impact on blood pressure. Thus, they represent the safest class – particularly among elderly and cardiovascular patients. Serotonin-Norepinephrine Reuptake Inhibitors, particularly venlafaxine, carry a greater risk of hypertension, possibly related to greater effects on the sympathetic nervous system. The Norepinephrine Reuptake Inhibitor reboxetine is considered a safe option because of its neutral effects on blood pressure in long-term studies, even if both hypotensive and hypertensive effects are reported. The Dopamine-Norepinephrine Reuptake Inhibitor bupropion can lead to blood pressure increases, usually at high doses, but may also cause orthostatic hypotension, especially in patients with cardiovascular diseases. The Norepinephrine-Serotonin modulators, mirtazapine and mianserin, have minimal effects on blood pressure, but may rarely lead to orthostatic hypotension and falls. These adverse effects are also observed with the Serotonin-Reuptake modulators, Nefazodone and Trazodone, but seldomly with Vortioxetine and Vilazodone. Agomelatine, the only melatonergic antidepressant drug, may also have limited effects on blood pressure. Tricyclic antidepressants have been associated with increases in blood pressure, as well as orthostatic hypotension, particularly imipramine. Oral monoamine-oxidase inhibitors, less frequently skin patch formulations, have been associated with orthostatic hypotension or, conversely, with hypertensive crisis due to ingestion of tyramine-containing food (i.e. cheese reaction). Lastly, hypertensive crisis may complicate antidepressant treatment as a part of the Serotonin Syndrome, also including neuromuscular, cognitive and autonomic dysfunction. Clinicians treating depressive patients should carefully consider their blood pressure status and cardiovascular comorbidities, because of the effects of antidepressant drugs on blood pressure profiles and potential interactions with antihypertensive treatments.